MAGYAR-SZERB GAZDASÁGI KAPCSOLATOK A MILOŠEVIĆI REZSIM BUKÁSÁT KÖVETŐEN - Bakó, Tamás (Közép-Európai Közlemények, 2019)
The aim of this study is to present the main events in the Hungarian-Serbian economic relations during the last two decades by summarizing the most important moments, their causes and consequences. After the fall of Milošević, it was necessary to re-establish the contractual relationship between the two countries and the corporate relationships terminated during the embargo. After the very promising start, the assassination of the Serbian prime minister, the constant domestic political crises, the government unwilling to make closer contacts, and according to the European standards the closed society of Serbia at that time, hasn’t become a political or economic ally of Hungary. In the time when the world economic conditions were in favour of overall development of bilateral economic relations. However the global economic crisis and recession has brought back not only the willingness to invest in Hungary, but also the bilateral trade. The historic reconciliation following the slow political rapprochement in 2014, has made the breakthrough, and contributed not only to the better enforcement of the Hungarian economic interests, but also to the prosperity of Hungarians in their native country, in Serbia. The Hungarian government is supporting Serbia’s EU integration process and in all foreign policy issues. As the result of this approach, there are no open questions between Budapest and Belgrade. The preconditions for the constant evolution of the economic relations without special support were the political gestures and friendly attitude of the two governments regarding the earlier sensitive questions and the national issues.